Characterization of white grubs (Melolonthidae: Coleoptera) at salak pondoh agroecosystem in Mount Merapi based on isozymic banding patterns - SRI WARDANI; SUGIYARTO SUGIYARTO (Smujo International, 2009)
Abstract. Wardani S, Sugiyarto. 2009. Characterization of white grubs (Melolonthidae: Coleoptera) at salak pondoh agroecosystem in Mount Merapi based on isozymic banding patterns. Nusantara Bioscience 1: 38-42. The aim of this research was to know the characteristics of white grubs (Melolonthidae: Coleoptera) based on isozyme banding patterns. This research was conducted at Sleman, Yogyakarta, and Magelang-Central Java for morphological purposes. The sample was taken from 5 places with different heights in which five samples were taken from each location. The method used in this research was polyacrylamide gel electrophoresis (PAGE) using the vertical type. The enzyme system used in this research were peroxidase and esterase to detect the isozyme banding patterns. The results showed a variation in isozyme banding patterns of white grubs (Melolonthidae: Coleoptera) at salak pondoh agroecosystem in Mount Merapi’s slope (peroxidase in station II and IV while esterase in station III and V). It means that genetic variation on the white grubs population at salak pondoh agroecosystem in Mount Merapi’s slope was found. The environmental condition also influenced the isozyme banding pattern’s appearance because each location had a different state.